Molecular screening of Hepatozoon in amphibian hosts - Babo, José Fernando Seabra (2014)
Parasite diversity has been poorly studied due to several factors, like the size of some species, location within the host, and the focus on groups with strong anthropogenic interests or with significant economic impact. Apicomplexa is a vast and diverse group of unicellular parasites with wide distribution and the most successful pathogen known to man. Within the group some genus have received little attention, like the case of Hepatozoon. They are poorly studied organisms requiring more sampling. Molecular screening techniques like PCR are quick and easy to use, and allow efficient detection of these parasites. It also allows sequencing which produce data for phylogenetic analyses. Nonetheless more data is necessary to correctly establish taxonomy and phylogenetic relations of the group. The aim of this work was to assess the diversity of parasites trough screening of tissue and blood samples from different amphibian species using specific parasite primers and reconstruct the phylogenetic relationships of the sequences produced. Several species of amphibians from Iberian Peninsula, Mediterranean Islands, Macaronesia region and Morocco were analyzed using specific parasite primers and blood smears were observed. Parasites were observed in several slides, with at least two Hepatozoon being identified, however primers fail to detect them. Only two parasites were amplified, a protozoan parasite, Ichthyopthirius multifiliis, identified in a Bufo calamita sample from Portugal, and a Apicomplexa parasite, Dactylosoma ranarum, in Pelophylax saharicus from Morocco. The primers used seem not to be useful with amphibians and new primers need to be developed to correctly assess the identity of the parasites observed In the smears.